Significancy and Subtancy of Civil Suit Compensation in Corruption Case where the Defendant was Acquitted by Judge - Alfon Alfon; Suhariningsih Suhariningsih; Bambang Sugiri; Prija Djatmika (BIRCU, 2020)
The spirit of Article 32 paragraph (2) of UU 31 / 1999 jo. UU 20 / 2001 means the country can use its right to a civil action for compensation for financial loss recovery state. The rationale for setting lawsuit replace losses in the article that indicates that in order to restore the country's financial losses due to corruption is not enough only in lean to the norms of criminal law. If the UU 31 / 1999 jo. UU 20/2001 categorized as Criminal Laws, then the regulation of a civil lawsuit in the Law, shows that a Prevailing Law may contain aspects of both criminal law and civil law. The study is the study of law by using the approach of Legislation, conceptual and historical approach. The results were obtained from studies of this are: 1) The specificity handling of corruption judging from the way the settlement; 2) The meaning and essence of civil suit for damages in the enforcement of the law on corruption. The civil lawsuit instrument is intended to maximize the return on state financial losses, because criminal efforts do not always succeed in recovering the entire state financial losses. The limitations of criminal law make criminal law instruments not the only one to solve the problem of returning state finances due to criminal acts of corruption.